ANALISIS PEMANFAATAN PENDAPATAN DESA TERHADAP CAPAIAN INDEKS DESA MEMBANGUN (IDM) DI KABUPATEN KUANTAN SINGINGI - Hermansyah Hermansyah; Syapsan Syapsan; Hendro Ekwarso (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to analyze the effectiveness of utilization, influence and determine the pattern of village income management in Kuantan Singingi Regency, the efforts and strategies undertaken to increase village income in Kuantan Singingi Regency. Data Collection Techniques: Documentation. Methods of Data Analysis using multiple linear regression analysis. The results show that the very effective PADesa of Kuantan Singingi Regency is caused by the realization of PADesa of Kuantan Singingi Regency which tends to reach the target and continues to increase. The cause of the realization of the Aid Fund and Revenue Sharing Fund never reaching the target of realizing village income was caused by several factors, the influence of village income on the achievement of the developing village index showed a significant 0.23 > 0.05, that Fcount > Ftable i.e. Fcount 0.23 > Ftable 0.05. Efforts made to increase the realization of aid funds and profit-sharing funds in Kuantan Singingi Regency included making several breakthroughs through several innovations but the efforts made were unable to increase the realization of aid funds and profit-sharing funds, this was due to the efforts made by planning , implementation, accountability and reporting, the Kuantan Singingi Regency government can provide rewards and sanctions if the realization targets that have been set are not achieved.